Anesthetic Management of the Hypertensive Patient: Part I - Yancey, Russell (Anesth Prog, 2018)
Hypertension is an important health challenge that affects millions of people across the world and is a major risk factor for cardiovascular disease. It is critical that anesthesia providers have a working knowledge of the systemic implications of hypertension. This review article will discuss the medical definitions of hypertension, the physiology of maintaining blood pressure, outpatient treatment of hypertension, anesthetic implications, and the common medications used by anesthesia providers in the treatment of hypertension. Part I will provide an overview of hypertension and blood pressure regulation. In addition, drugs affecting predominantly renal control of hypertension, such as diuretics, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and renin-inhibiting agents, will be discussed. In part II, the remaining major antihypertensive medications will be reviewed as well as anesthetic implications of managing patients with hypertension.